Interaction of Host miRNA and Viral RNA of Hepatitis C Virus as New Drug Targets Against Development of Hepatocellular Carcinoma - Reshu Chauhan; Vinod Joshi; Bennet Angel; Annette Angel; Mohammed Buvvaji, Shareef; Vikram Singh Chauhan; Aarya Chitransh; Khushbu Kumari; Lalmalsawmi Sailo (Science & Technology Asia, 2025)
Hepatitis C virus (HCV) infection induces significant changes in hepatocytes over time. Host-derived microRNAs (miRNAs), small non coding RNAs ( 22 nucleotides), are believed to influence the persistence or suppression of chronic HCV infection by modulating viral genome replication, transcription, and translation. However, their contribution to the development of hepatocellular carcinoma (HCC), as well as the specific interactions between miRNAs and distinct HCV genotypes, remain insufficiently understood. This study explores the potential involvement of host miRNAs in HCC progression among patients infected with different HCV genotypes. Using various bioinformatics tools—such as Clustal Omega, ChimeraX: AlphaFold, EMBOSS Transeq, UNAFOLD, and Freiburg IntaRNA—we analyzed the site-specific binding of key miRNAs (miR-122, miR-21, miR-155, and miR-193a-5p) across all seven HCV genotypes. Our findings revealed that miR-122 predominantly targets the NS5B coding region in most genotypes, suggesting a role in inhibiting viral replication and translation. Conversely, certain miRNAs that bind to the Envelope (E) region may enhance viral gene expression. These results indicate that sequence homology between host miRNAs and HCV mRNA can either suppress or facilitate viral gene translation. Targeting miRNAs that promote HCV replication may offer a novel therapeutic strategy for managing HCV-related diseases.